Emotional Intelligence and Role Conflict a Bond of Converse Relationship: Evidence from the Hospitals Sector of the Health Industry - Rafiq, Dr. Imran; Aleem, Muhammad; Aqdas, Dr Ramaisa; Ziauddin; Abdullah, Dr Nik Ab Halim bin Nik (The journal of contemporary issues in business and government, 2022)
This research study aimed at finding the convers relationship of emotional intelligence and role conflict at the hospitals of Peshawar, KPK, Pakistan. Emotional intelligence is considered the best coping strategy to deal with work stress, while role conflict is the most common practicing stressor that contributestothe stressful condition of a person. Hospitals are the most crowded and overburdened sector of any nation that is heavily dependent on multiple roles of nurses, doctors, and medical staff. The objective of this research was to see the effect of emotional intelligence in dealing with role conflict of the nurses and medical staff of three big hospitals in the city. The results show a significant inverse relationship between emotional intelligence and role conflict. The P-Value (0.000), T-statistics (16), R-Square (0.32) and path coefficients (-0.56)show highly significant results of underline relationships. For these findings, SmartPLS 3.0 was used to analyze the response of 359 nurses and medical staff employing stratified sampling and systematic random sampling techniques on a five-point scale of adapted questionnaires.